Volatility and Comovement in a Globalized World Economy : An Empirical Exploration - Kose, Ayhan (IMF Working Papers; Working Paper ;, 2003)
This paper analyzes the evolution of volatility and cross-country comovement in output, consumption, and investment fluctuations using two distinct datasets. The results suggest that there has been a significant decline in the volatility of business cycle fluctuations and a slight increase in the degree of cyclical comovement among industrialized countries over time. However, for emerging market economies, financial globalization appears to have been associated, on average, with an increase in macroeconomic volatility as well as declines in the degree of comovement of output and consumption growth with their corresponding world aggregates.